The Effect of Flipchart-Based Health Education on Knowledge and Self-Efficacy Regarding High-Risk Pregnancy among Pregnant Women - Sri Hardi Wuryaningsih; Adin Mu’afiro; Miadi; Nimas Dhalita Audria Hanun (International Journal of Advanced Health Science and Technology, 2026)
Maternal mortality remains a major public health challenge in Indonesia, and limited knowledge of high-risk pregnancy is one of the factors that may delay appropriate decision-making and reduce women’s confidence in managing pregnancy-related complications. This study aimed to examine the effect of flipchart-based health education on the knowledge and self-efficacy of pregnant women regarding high-risk pregnancy. A pre-experimental study with a one-group pretest-posttest design was conducted at the Kapas Health Center, Bojonegoro Regency. The population consisted of 302 pregnant women, and a sample of 51 participants was selected using the Lemeshow formula. The independent variable was health education delivered through flipchart media, while the dependent variables were knowledge and self-efficacy regarding high-risk pregnancy. Data were collected using structured questionnaires and analyzed using the Wilcoxon signed-rank test with a significance level of 0.05. The results showed a statistically significant improvement in knowledge after the intervention (p = 0.008). Before the intervention, 27 participants (53%) had poor knowledge, 20 (39.2%) had adequate knowledge, and 4 (7.8%) had good knowledge. After the intervention, the proportion with poor knowledge decreased to 16 participants (31.4%), while 24 (47%) had adequate knowledge and 11 (21.6%) had good knowledge, indicating that 68.6% achieved adequate-to-good knowledge after the intervention. A significant improvement was also observed in self-efficacy (p = 0.000). Prior to the intervention, 12 participants (23.5%) had low self-efficacy and 39 (76.5%) had high self-efficacy; after the intervention, all participants (100%) demonstrated high self-efficacy. In conclusion, flipchart-based health education was effective in improving both knowledge and self-efficacy among pregnant women regarding high-risk pregnancy. This approach may serve as a practical, low-cost, and accessible educational strategy for use in community health centers to support better maternal awareness, confidence, and decision-making.